2010
DOI: 10.1039/b920113k
|View full text |Cite
|
Sign up to set email alerts
|

Tröger’s base-functionalised organic nanoporous polymer for heterogeneous catalysis

Abstract: An organic nanoporous polymer (BET surface area of 750 m(2) g(-1)) containing bicovalently-bonded Tröger's base as functional moieties in the network was synthesized, characterised, and further applied as a promising heterogeneous catalyst in the addition reaction of diethylzinc to aromatic aldehyde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
135
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 222 publications
(136 citation statements)
references
References 25 publications
(20 reference statements)
0
135
0
1
Order By: Relevance
“…Recently, a few examples of CMPs showing catalytic activity have been reported. [10,17] Polymer C contains a cyclometalated Ir III complex which is closely related to a class of successful reductive amination catalysts. [18] We therefore examined the heterogeneous catalytic activity of the CMP-CpIr networks.…”
mentioning
confidence: 99%
“…Recently, a few examples of CMPs showing catalytic activity have been reported. [10,17] Polymer C contains a cyclometalated Ir III complex which is closely related to a class of successful reductive amination catalysts. [18] We therefore examined the heterogeneous catalytic activity of the CMP-CpIr networks.…”
mentioning
confidence: 99%
“…Since then, various of TB derivatives were synthesized and applied in the eld of molecular recognition [2], chiral ligands [3][4][5], DNA probes [6,7], stereo selective catalysis [8][9][10][11][12], drug development [13,14], CO 2 capture [15,16], bioorganic chemistry [17][18][19], electroluminescent materials [20,21] and supra molecular chemistry [22] in the last two decades. Their wide range of applications is based on their huge rigidity, V-shaped twisted con guration, N-central chirality and C 2 -symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…8 There are some reports in the literature on different applications of polymers containing Trö ger's base, which have conformationally and geometrically well-defined linker. 9,10 Because this unit has good ability to prevent the close packing of chains and decreases interchain interaction, it has been suggested that synthetic polymers, containing Trö ger's unit, can be dissolved by organic solvents. Thus, the presence of the Vshaped Trö ger's unit in the final macromolecules was thought to lead to obtain amorphous polyhydrazides, which have high solubility in organic solvents, low softening temperatures, good thermal and mechanical properties, and easy melt processability.…”
Section: Introductionmentioning
confidence: 99%